Analysis of the Mechanical Behavior of Prefabricated Wattle and Daub Walls - Cuitiño Rosales, Maria Guadalupe (2014)
This paper summarizes an extensive research about mechanical strength of wattle and daub walls, employed in natural construction. Prefabricated wattle and daub walls, corresponds to the constructive system of frameworks, the perimeter of the walls of enclosures are composed of a wooden frame and the interior is a framework of Castilla canes, to eventually be covered with a mud mixture with clay, sand and vegetable fiber. Building with wattle and daub, is used worldwide, nevertheless, scant information is available about the strength of the walls against compressive and cutting loads. To gather more information about this, prefabricated wattle and daub walls were built in real scale 1:1, and tested in the University structures laboratory. Was obtained that walls have a ultimate compressive strength of 1.56MPa and the average shear strength is 0.13MPa, these values are higher than adobe's values and is recommended this natural construction in areas with earthquakes because its flexibility instead of adobe. These data are valuable for structural calculations of wattle and daub houses and make safer homes.